About lost futures or the political heart of history - Mudrovcic, María Inés (Historein, 2013)
This article attempts to show that in western societies of today, in the absence of absolute foundations and the lack of a frame of meaning that opens new horizons of expectations, a political self understanding of the present in terms of past, begins to emerge. This is possible because the major “catastrophes” of the 20th century have not established a rupture between past and present on the political plane. What I am trying to show here is that the kind of break between past and present made possible by events such as the French Revolution and the Fall of the Soviet Union, took place because these events provoked political ruptures. Because the catastrophes of the 20th century did not break the political order which gave them birth (the modern secular state), they have created an order of time which, without leaving the future aside, feeds itself from the past.